A comprehensive analytical approach for monitoring the physico-chemical changes of the paintings after exposure to environmental risks. Issue 1 (2nd January 2021) - Ibrahim, Medhat; Issa, Yousry M.; Abdel-Maksoud, Gomaa; Magdy, Mina
Abstract: The study is composed of three phases to describe the paintings at normal and several aging times: modeling of new icons similar to an ancient one, aging of the icons by heat and ultraviolet irradiation, and characterization of the icons. The results showed a change in the chemical structure of the painting materials, the crystallinity of the wood and canvas materials, and the chromaticity coordinates with darkening in the heat treatment and fading in the UV irradiation treatment. There is a correlation between the exposure time, the chemical properties of the materials, and the optical properties of the paintings.